Enhanced Photoresponse and Surface Wettability of Bi2Se3 Film with Annealing at Different Temperatures for Optoelectronic Applications - Das, Subhashree; Dandasena, Banaja; Alagarasan, Devarajan; Naik, Ramakanta (ACS applied optical materials, 2024)
The current investigation focuses on Bi2Se3 films grown via a thermal evaporation process and subsequently annealed at temperatures of 100 °C, 150 °C, 200 °C, and 250 °C for 2 h. The structural study of the Bi2Se3 annealed film confirmed the crystalline nature of the material, and crystallite sizes ranged between 14 and 24 nm. Annealing induced enhanced porosity, which was observed through surface morphology analysis. Optical studies revealed decreased transmission ability and increased absorption capability with postannealing. The direct optical band gap reduced from 1.269 to 1.144 eV at 250 °C due to increased localized states within the gap. Annealing also led to an enhancement in the extinction coefficient and optical density, alongside a reduction in skin depth. The material’s refractive index gradually enhanced with the increase in the annealing temperature. The refractive index of the material gradually increased with higher annealing temperatures. Additionally, the third-order susceptibility rose from 4.304 × 10–11 to 5.661 × 10–11 esu, resulting in an increase in the nonlinear refractive index from 5.152 × 10–10 to 6.575 × 10–10 esu, respectively. Moreover, annealing increased the hydrophobicity of the films, rendering them as self-cleaning materials. The surface energies of the materials lie between 14.05 and 4.49 mN/m. The augmented photocurrent postannealing indicates potential applications in various photodetector sectors. These findings, which highlight optical and structural enhancements, underscore the suitability of these films for optoelectronic devices.